Alternative Dorsal Root Ganglion Neuromodulation Electrode Implantation: A Report of 2 Cases with 3 Different Techniques - Schultheis, Björn Carsten; Wille, Christian; Ross-Steinhagen, Nikolas Eugenio; De Ridder, Dirk; Vancamp, Tim; Weidle, Patrick A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims The traditional percutaneous placement of dorsal root ganglion (DRG) electrodes may not be eligible for every patient. In this tertiary spine surgery and interventional pain therapy center, alternative neurostimulation implantation techniques were developed and applied where standard percutaneous approaches failed or were contraindicated.Case presentation Three alternative implantation techniques can be used: (1) open surgical placement of DRG leads, (2) two-lead insertion via a lateral to medial transforaminal approach (level L3), and (3) percutaneous approach with two leads close to the spinal nerves L4 (peripheral nerve stimulation).Results The placement of the leads occurred without complications and resulted in similar expected outcomes as with the common percutaneous technique with long-term stable pain suppression at 7 months and 1 year.Conclusions In patients in whom the DRG cannot be approached by the standard percutaneous approach, at least three alternatives may be used in experienced hands resulting in stable pain suppression of similar magnitude.
Keywords: dorsal root ganglion; alternative implantation techniques; neuropathic pain; total knee arthroplasty; peripheral nerve stimulation